PERAN DUKUNGAN SOSIAL TERHADAP STRES KERJA SEBAGAI PENINGKATAN KINERJA KARYAWAN - CAHYANI, WELSYA; FRIANTO, AGUS (Jurnal Ilmu Manajemen (JIM), 2019)
Into in an industrial revolution 4.0 era that demands human resources in the mastery of technology that makes companies must be more competitive in competition. Companies must be able to develop their quality human resources, and have the potential for achieve goals, mindsets and innovations that come from individual in the company capable of creating success the company. The research aims to determine and explain the effect of Work Stress, Employee Performance and Social Support, this study uses quantitative. The sample technique is using saturated samples with 44 respondents in the distribusi and niaga employees of PT. PLN (Persero) Unit Induk Distribusi Jatim. The statistical analysis used is Partial Least Square (PLS) with the support of smartPLS 3.0 software. The results of this research shows work stress has no significant effect on employee performance. And Social support moderates Work Stress on Employee Performance.